Neutrosophic fuzzy metric spaces and fixed points for contractions of nonlinear type - Ayman A. Hazaymeh; Anwar Bataihah (Neutrosophic Sets and Systems)
In this research, we present xed point theorems pertaining to nonlinear contractions, situated within the sophisticated framework of neutrosophic fuzzy metric spaces. Furthermore, we establish several xed point results that are pertinent to this speci c context.